1965
DOI: 10.1017/s0016672300004249
|View full text |Cite
|
Sign up to set email alerts
|

The use ofp-fluorophenylalanine with ‘master strains’ ofAspergillus nidulansfor assigning genes to linkage groups

Abstract: Four ‘master’ strains of Aspergillus nidulans, three of which are marked on each of the eight chromosomes, are used for assigning genes of unknown location to linkage groups. In this technique a heterozygous diploid is synthesized between one ‘master’ strain and a strain carrying an unlocated marker. This diploid is haploidized by growth on p-fluorophenylalanine, and the haploids thus obtained are classified for recombination between the unlocated marker and each of the markers of the ‘master’ strains. The mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(80 citation statements)
references
References 11 publications
1
79
0
Order By: Relevance
“…Therefore, a diploid between an acuN356 strain and the strain MSF with each linkage group genetically marked was constructed and subjected to haploidization analysis (McCully and Forbes 1965). This revealed that the acuN356 strain contained a translocation event involving linkage groups I and V. Southern blot analysis of HindIII-and HaeIII-digested acuN356 DNA, using cloned acuN DNA as a probe, localized a translocation breakpoint to the 59 region of acuN $150-300 bp upstream of the predicted enolase ATG (Figure 1 and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a diploid between an acuN356 strain and the strain MSF with each linkage group genetically marked was constructed and subjected to haploidization analysis (McCully and Forbes 1965). This revealed that the acuN356 strain contained a translocation event involving linkage groups I and V. Southern blot analysis of HindIII-and HaeIII-digested acuN356 DNA, using cloned acuN DNA as a probe, localized a translocation breakpoint to the 59 region of acuN $150-300 bp upstream of the predicted enolase ATG (Figure 1 and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Linkage was also indicated for acrA withpA, acrA with lacA, and SA with riboB. It is unlikely that linkage is involved, though, as haploidization should lead to the assortment of complete linkage groups (McCully & Forbes, 1965). Mitotic recombination should only disrupt such linkages in approximately 1% of haploidization events (Kafer, 1961(Kafer, , 1977.…”
Section: Haploidization and Chromosome Assaymentioning
confidence: 99%
“…Haploidization analysis (McCully & Forbes, 1965) showed that bzuAI was located in linkage group IV, and approximately 22 % recombination with mauAz was detected in sexual crosses. Strains containing gmdAI grew poorly on benzamide, phenylacetamide and some other amides as sole nitrogen sources (see below).…”
Section: Initial Characterization Of Mutantsmentioning
confidence: 99%